Perception of Agricultural Students and Agro-professionals towards Agricultural Education and Skill Development in India: Connect and Disconnect (Indian Journal of Extension Education, 2015)
India is entering in phase of demographic dividend. Presently, India has more than 50 per cent of its population within the age group of 15 to 59 and 28 percent of population in age group of 15-29. Furthermore, by 2020, more than 65 percent of Indian population will be under working age group. Manpower availability in agricultural sector indicated that more than 12000 agricultural graduates pass out from the state agricultural universities (SAUs) all over the country every year, of which only 2000 find job in private and public sector, leaving a huge number of graduates unemployed. This agricultural demographic dividend may become an asset as well as liability for Indian agriculture, depending upon the extent of skill development among agricultural students. For capturing perception of agricultural students, data has been gathered from 100 agricultural students comprising from State Agricultural Universities, MANAGE and ICAR-IARI. To analyze the perception of agro-professionals, 25 Kisan Call Centre level- I graduate employees and 25 agro entrepreneur were interviewed. The present study has analyzed the existing perception of agricultural students and agro-professionals towards agricultural education and skill development in India. Respondents have shown high importance level towards core employability skills, professional skills and communication skills however respondents perceived that the implementation level of core employability skills, professional skills and communication skills in Indian agricultural education system is low. Skill gap analysis has shown that there is high skill gap in four core employability skills (team work, entrepreneurship, practical application and self-motivation), three professional skills (creativity, problem solving ability and statistical competence) and three communication skills (verbal communication, non-verbal communication and technical writing) and these skills needs to be given more importance in agricultural education system in India.